Three‐dimensional extrusion bioprinting of single‐ and double‐network hydrogels containing dynamic covalent crosslinks. Issue 4 (23rd January 2018) - Wang, Leo L.; Highley, Christopher B.; Yeh, Yi‐Cheun; Galarraga, Jonathan H.; Uman, Selen; Burdick, Jason A.
Abstract: The fabrication of three‐dimensional (3D) scaffolds is indispensable to tissue engineering and 3D printing is emerging as an important approach towards this. Hydrogels are often used as inks in extrusion‐based 3D printing, including with encapsulated cells; however, numerous challenging requirements exist, including appropriate viscosity, the ability to stabilize after extrusion, and cytocompatibility. Here, we present a shear‐thinning and self‐healing hydrogel crosslinked through dynamic covalent chemistry for 3D bioprinting. Specifically, hyaluronic acid was modified with either hydrazide or aldehyde groups and mixed to form hydrogels containing a dynamic hydrazone bond. Due to their shear‐thinning and self‐healing properties, the hydrogels could be extruded for 3D printing of structures with high shape fidelity, stability to relaxation, and cytocompatibility with encapsulated fibroblasts (>80% viability). Forces for extrusion and filament sizes were dependent on parameters such as material concentration and needle gauge. To increase scaffold functionality, a second photocrosslinkable interpenetrating network was included that was used for orthogonal photostiffening and photopatterning through a thiol‐ene reaction. Photostiffening increased the scaffold's modulus (∼300%) while significantly decreasing erosion (∼70%), whereas photopatterning allowed for spatial modification of scaffolds with dyes. Overall, this work introduces a simple approach to both fabricate and modify 3D printed scaffolds. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 865–875, 2018.